APLIKASI SIMODAS UNTUK PENENTUAN HIDROGRAF BANJIR DI DAERAH ALIRAN SUNGAI (DAS) LOKOTENIHAWU PULAU SABU NUSA TENGGARA TIMUR - Fanny Tri Raditya (Jurnal Ilmiah Media Agrosains, 2014)
River flood discharge is an indicator of the ability of a watershed to collect and drain rainwater. Of flood discharge is known to regulate the ability of a watershed hydrologic process. Information flood discharge can be used as a reference to estimate the maximum flood that occurred in a watershed. SIMODAS is software that can be used as information systems and hydrologic models for watershed management. This software is developed by integrating hydrologic models and spatial spread of Geographical Information Systems (GIS). This study aims to predict the flood hydrograph at the Lokotenihawu watershed, Sabu Island, Nusa Tenggara Timur using SIMODAS. The method used in this study is to estimate the spatial analysis of flood hydrograph at the Lokotenihawu watershed, Sabu Island, Nusa Tenggara Timur. Based on the results of the simulation models, it is known: 1) hydrograph obtained using SIMODAS in Lokotenihawu watershed having a hydrograph ordinate rapid rise but long descent. With a peak discharge of 9.322 m3/second and a volume of 338,400 m3. 2) SIMODAS is a model that has the ability to get data closer to field conditions, this is because SIMODAS an integration of hydrologic models with a geographic information system that can accommodate changes in the spatial interactive watershed.